2016
DOI: 10.1039/c5lc01297j
|View full text |Cite
|
Sign up to set email alerts
|

An inverted dielectrophoretic device for analysis of attached single cell mechanics

Abstract: Dielectrophoresis (DEP), the force induced on a polarizable body by a non-uniform electric field, has been widely used to manipulate single cells in suspension and analyze their stiffness. However, most cell types do not naturally exist in suspension but instead require attachment to the tissue extracellular matrix in vivo. Cells alter their cytoskeletal structure when they attach to a substrate, which impacts cell stiffness. It is therefore critical to be able to measure mechanical properties of cells attache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 107 publications
(133 reference statements)
1
6
0
Order By: Relevance
“…The R 2 value obtained from the two curves were >0.98, indicating good fit for the data. Similar to the findings reported in [22, 47], the DEP method was found to yield a higher force value as compared to other characterization methods such as AFM.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The R 2 value obtained from the two curves were >0.98, indicating good fit for the data. Similar to the findings reported in [22, 47], the DEP method was found to yield a higher force value as compared to other characterization methods such as AFM.…”
Section: Resultssupporting
confidence: 87%
“…They concluded that bead attachment could strongly affect the force applied to the cells, and increased stress in magnetic cytometry could reinforce nonlinearity and cellular plasticity. Urbano et al [22] examined attached epithelial cells by using DEP pushing and AFM indentation method and found that the elastic modulus differed by at least 10 times. Fortier et al [50] used AFM to characterize leukemia cells with two different probes and they found that the elastic moduli evaluated from a conical probe were larger, and their distribution was wider, as compared to the results from a spherical probe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An optimum electrode configuration is the one that is less detrimental to the cells and provides the largest elongation under similar conditions (applied voltage and frequency) for the same cell and medium. We studied six configurations based on different configurations studied in other literature 22 26 , including rectangular, elliptical, triangular, and combinations, depicted in Fig. 4 b.…”
Section: Resultsmentioning
confidence: 99%
“…At low frequencies (lower than 100 kHz) direct contact between electrodes and the fluid leads to bubbles. In previous studies 25 , 26 , hydrogenated silicon nitride has been used as a passivation layer to avoid the formation of bubbles. Here, we used diluted SU8 (MicroChem) by cyclopentanone as a passivation layer (Fig.…”
Section: Methodsmentioning
confidence: 99%